2020
DOI: 10.1111/anae.14983
|View full text |Cite
|
Sign up to set email alerts
|

Regional anaesthesia practice for arteriovenous fistula formation surgery

Abstract: Summary We conducted a survey and semi‐structured qualitative interviews to investigate current anaesthetic practice for arteriovenous fistula formation surgery in the UK. Responses were received from 39 out of 59 vascular centres where arteriovenous access surgery is performed, a response rate of 66%. Thirty‐five centres reported routine use of brachial plexus blocks, but variation in anaesthetic skill‐mix and practice were observed. Interviews were conducted with 19 clinicians from 10 NHS Trusts including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Most AVF in the UK are currently created under either LA or RA. 20 Several non-randomised 21,22 and subsequent small randomised studies suggested better early patency rates for AVF created under RA. 23e25 Our (AJRM, EA) single-centre randomised controlled trial (n¼126) remains the largest to date and showed better early to medium term (3 months) patency rates for AVF created under a single-shot brachial plexus block compared to LA (84% vs 62%; odds ratio [OR] 3.3 [95% CI 1.4 to 7.6] p¼0.005).…”
Section: Local Versus Regional Anaesthesiamentioning
confidence: 99%
“…Most AVF in the UK are currently created under either LA or RA. 20 Several non-randomised 21,22 and subsequent small randomised studies suggested better early patency rates for AVF created under RA. 23e25 Our (AJRM, EA) single-centre randomised controlled trial (n¼126) remains the largest to date and showed better early to medium term (3 months) patency rates for AVF created under a single-shot brachial plexus block compared to LA (84% vs 62%; odds ratio [OR] 3.3 [95% CI 1.4 to 7.6] p¼0.005).…”
Section: Local Versus Regional Anaesthesiamentioning
confidence: 99%
“…Decisions about the mode of anesthesia depend on a number of interrelated factors, including expertise, inclination, habit, practicality, and norms. 14…”
Section: Regional Block or Local Anesthesiamentioning
confidence: 99%
“…Supraclavicular block is the most common and preferred anesthesia method for arteriovenous (AV) fistula formation surgery [ 1 ]. Since nerve blocks tend to increase vasodilation, blood flow, and tissue oxygenation during autogenous AV fistula creation, they improve the successful rate of fistula [ 2 ].…”
Section: Introductionmentioning
confidence: 99%